Improved Carrier Buffer for AC Arc Direct Reading Atomic Emission Spectrometry Based on the SEM Technique - QIU Hong-xi; ZHAO Gang; LIU Jiu-fen; LI Ke-yong; LONG Zhi-wu; LI Zhi-xiong; XIANG Mao-bi; LIU Wei-hong (Yankuang ceshi, 2018)
Powder solid sampling atomic emission spectrometry is a simple sample pretreatment method with high sensitivity, low detection limit, and little environmental pollution. This method has been applied to the simultaneous analysis of trace Ag, B and Sn in geochemical samples. However, the serious matrix effect limits the application of this method. Based on the Scanning Electron Microscopy (SEM) technique, the differences in the composition of the reaction products at different times for specific formulations and different samples was compared. Combined with the evaporation curve to reverse the reaction process, a carrier buffer suitable for different types of geochemical samples was developed. In order to realize the improvement of the arc burning process, K2S2O7 and NaF were used as flux during preparing carrier buffer to catalytically decompose the matrix. Synergizing with PTFE and sedimentation S promotes rapid evaporation of analyzed elements in various forms. The formation of Al2O3-SiO2-CaO-BaO mutual melt lowers the Tammann temperature and can absorb matrix oxides in-situ, suppressing the interferences. Compared with the available method, the sensitivity increased by 1.2 times, and the precision, accuracy and detection limit are superior to a number of geochemical survey specifications.